2003
DOI: 10.1001/archotol.129.11.1207
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Antibiotic Therapy for Deep Neck Abscesses Defined by Computed Tomography

Abstract: In a select number of clinically stable children, deep neck abscesses diagnosed on contrast-enhanced CT scans using strict radiographic criteria can be effectively treated with intravenous antibiotics alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 25 publications
4
86
1
3
Order By: Relevance
“…Mcclay et al [35] showed resolution of deep neck abscesses with intravenous antibiotics alone, but in our case there was a radiological evidence of spinal cord compression by the expanding abscess. So with this in mind and together with the family's objection to invasive surgery, we opted for aspiration of the abscess to obtain a sample and indirectly decompress the spinal cord.…”
Section: Rationale For Treatment and Evidence-based Literaturecontrasting
confidence: 60%
“…Mcclay et al [35] showed resolution of deep neck abscesses with intravenous antibiotics alone, but in our case there was a radiological evidence of spinal cord compression by the expanding abscess. So with this in mind and together with the family's objection to invasive surgery, we opted for aspiration of the abscess to obtain a sample and indirectly decompress the spinal cord.…”
Section: Rationale For Treatment and Evidence-based Literaturecontrasting
confidence: 60%
“…Although CT is helpful both in determining the presence and location of neck infections in children, it is less helpful in differentiating abscess from lymphadenitis and cellulitis. We found false positive rates as 6.5% while Publications have reported false-positive rates of up to 25% when CT scans are used to diagnose paediatrics neck abscesses [33] . On the other hand, use of MRI gives improved soft tissue definition without the use of radiation but its use is limited due to the lack of availability and cost.…”
Section: Complicationsmentioning
confidence: 55%
“…McClay et al claim that children with infections of the deep spaces of the neck can be treated successfully only conservatively (antibiotic therapy) [36]. Similar observations were reported by Page et al, who believe that small retropharyngeal abscesses in children can be treated conservatively [5].…”
Section: Discussion and Literature Reviewmentioning
confidence: 74%